Effects of Curcuminoids on Frequency of Acute Myocardial Infarction After Coronary Artery Bypass Grafting - Wongcharoen W. (2014)
It is well established that myocardial infarction (MI) associated with coronary artery bypass grafting (CABG) predicts a poor outcome. Nevertheless, cardioprotective therapies to limit myocardial injury after CABG are lacking. Previous studies have shown that curcuminoids decrease proinflammatory cytokines during cardiopulmonary bypass surgery and decrease the occurrence of cardiomyocytic apoptosis after cardiac ischemia/reperfusion injury in animal models. We aimed to evaluate whether curcuminoids prevent MI after CABG compared to placebo. The 121 consecutive patients undergoing CABG were randomly allocated to receive placebo or curcuminoids 4 g/day beginning 3 days before the scheduled surgery and continued until 5 days after surgery. The primary end point was incidence of in-hospital MI. The secondary end point was the effect of curcuminoids on C-reactive protein, plasma malondialdehyde, and N-terminal pro-B-type natriuretic peptide levels. Baseline characteristics were comparable between the curcuminoid and placebo groups. Mean age was 61 ± 9 years. On-pump CABG procedures were performed in 51.2% of patients. Incidence of in-hospital MI was decreased from 30.0% in the placebo group to 13.1% in the curcuminoid group (adjusted hazard ratio 0.35, 0.13 to 0.95, p = 0.038). Postoperative C-reactive protein, malondialdehyde, and N-terminal pro-B-type natriuretic peptide levels were also lower in the curcuminoid than in the placebo group. In conclusion, we demonstrated that curcuminoids significantly decreased MI associated with CABG. The antioxidant and anti-inflammatory effects of curcuminoids may account for their cardioprotective effects shown in this study. © 2012 Elsevier Inc. All rights reserved.